2020
DOI: 10.1177/0954406220917717
|View full text |Cite
|
Sign up to set email alerts
|

Additive manufacturing and topology optimization: A design strategy for a steering column mounting bracket considering overhang constraints

Abstract: In the present paper, the use of the topology optimization in a metal Additive Manufacturing application is discussed and applied to an automotive Body-in-White component called dash. The dash is in the front area of the Body-in-White, between the left-hand-side shock-tower and the Cross Car Beam, and its task is to support the steering column. The dash under investigation is an asymmetric rib-web aluminium casting part. The influence of Additive Manufacturing constraints together with modal and stiffness targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
(178 reference statements)
0
11
0
1
Order By: Relevance
“…The assembly includes: a Cross-Car beam (CCB), two lower extrusions, the vertical pillar connecting the CCB to the tunnel, two lateral castings connecting the CCB to the front hinge pillars, the Steering Column Support (SCS), and the steering column sub-assembly, see Figure 4(a) and Figures 1 to 3 in Mantovani et al 26 All the extruded parts are shown in green, the castings are in red, while the sheets are shown in blue. The extruded and the sheets parts are modelled with four-noded isoparametric shell elements with an average size of 4 mm.…”
Section: Reference Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly includes: a Cross-Car beam (CCB), two lower extrusions, the vertical pillar connecting the CCB to the tunnel, two lateral castings connecting the CCB to the front hinge pillars, the Steering Column Support (SCS), and the steering column sub-assembly, see Figure 4(a) and Figures 1 to 3 in Mantovani et al 26 All the extruded parts are shown in green, the castings are in red, while the sheets are shown in blue. The extruded and the sheets parts are modelled with four-noded isoparametric shell elements with an average size of 4 mm.…”
Section: Reference Modelmentioning
confidence: 99%
“…18,19 Several algorithms have been introduced to overcome AM production constraints in TO, using Solid, Isotropic Material with Penalization (SIMP) or level-set method. [20][21][22][23][24][25] Mantovani et al 26 adopted an AM-oriented TO in the design of an automotive steering column bracket to reduce the amount of support structures that are discarded at the end of the process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, some limitations of the Standard suggests the need for further developments. The proposed Standard can handle only voxel-based lattice structures 20 of the strut-and-node arrangement type, while it is still not able to model other kinds of periodic shapes, such as Triply Periodic Minimal Surface (TPMS) structures. A reduced portfolio of unit cell types (Figure 3) and cross-section topologies is noticed in this first embodiment of the Standard and add-on developed for its testing.…”
Section: Case Studymentioning
confidence: 99%
“…For further details about this kind of structures, the reader is addressed to the source. 20 Conformal lattice structures. The last type of lattice considered in this project is the conformal one.…”
Section: Graded Lattice Structures a Similar Table Is Developedmentioning
confidence: 99%
“…In this contribution, a methodology similar to the one presented by Barbieri et al 27,28 and Mantovani et al 29 was applied to determine the optimal material distribution for an upright to be produced in aluminum alloy by laser-powder bed fusion (L-PBF). 30 L-PBF discloses extreme freedom in geometry, which also enables the production of the complicated shapes resulting from TO.…”
Section: Introductionmentioning
confidence: 99%